(untitled) (Journal of Comparative & International Higher Education, 2024)
This study maps the types of international involvement opportunities available to HESA: Higher Education and Student Affairs graduate students in the U.S.A., as seen through the eyes of the students, and analyzes the impact of these students’ diverse international involvements on their orientation towards social responsibility. The study follows a survey research design. The study’s results indicate low levels of international exposure amongst HESA graduate students across diverse programs, and moderate rates of orientation towards civic responsibility. HESA students’ orientation towards social responsibility can successfully be predicted by a combination of five variables, three of which represent curricular and co-curricular environmental engagements: listening to an international speaker, discussing the ways the U.S. higher education links to the rest of the world, and attending presentations of study abroad students. The findings aim to inform program directors and faculty on existing opportunities for international exposure, on the rate of student involvements in them, as well on the importance of international exposures for their students’ future professional preparation.